2007
DOI: 10.1080/14034940601048091
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychosocial work conditions on attempted and completed suicide among western Canadian sawmill workers

Abstract: This study indicates that workers with poor psychosocial working conditions may be at increased risk of both attempted and completed suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 28 publications
4
53
0
1
Order By: Relevance
“…Results from the analyses we conducted support the notion that workers in certain occupations may be at higher risk of suicide due to a range of work exposures and to work related stress [Ostry et al, 2007;Bartram and Baldwin, 2010;Takusari et al, 2011].…”
Section: Discussionsupporting
confidence: 76%
“…Results from the analyses we conducted support the notion that workers in certain occupations may be at higher risk of suicide due to a range of work exposures and to work related stress [Ostry et al, 2007;Bartram and Baldwin, 2010;Takusari et al, 2011].…”
Section: Discussionsupporting
confidence: 76%
“…These 22 studies have been conducted in a variety of locations, including Germany,16 26 Norway,27 South Korea,28 29 the USA,30–32 France,33 China (Hong Kong Special Administrative Region),34 Australia,15 35 36 Canada37 and Sweden 38. There were two studies that reported data from more than one sample, one study reported data from Italy and Sweden39 and the second included data from Australia, China, Germany and South Korea 14…”
Section: Resultsmentioning
confidence: 99%
“…A recent review indicated that work-related stress is associated with increased risk of depression, anxiety, aggression, fatigue and burnout, as well as unhealthy behaviours such as increased alcohol use, smoking, infrequent exercise, poor diet and disturbed sleep (Leka & Jain, 2010). Work-related stress has further been linked to relationship difficulties (Story & Repetti, 2006) and risk of suicidal behaviours (Ostry et al, 2007). Despite evidence of elevated distress among Australian law students and the adverse effects of stress on personal and professional functioning, there is limited research into the relationship between stress in law school and adjustment outcomes in law students.…”
mentioning
confidence: 99%